Targeting Epigenetic Mechanisms in Vascular Aging - Lin, Zhongxiao; Ding, Qian; Li, Xinzhi; Feng, Yuliang; He, Hao; Huang, Chuoji; Zhu, YiZhun (Frontiers in Cardiovascular Medicine, 2022)
Environment, diseases, lack of exercise, and aged tendency of population have becoming crucial factors that induce vascular ageing. Vascular ageing is unmodifiable risk factor for diseases like diabetes, hypertension, atherosclerosis, and hyperlipidemia. Effective interventions to combat this vascular function decline is becoming increasingly urgent as the rising hospitalization rate caused by vascular ageing-related diseases. Fortunately, recent transformative omics approaches have enabled us to examine vascular ageing mechanisms at unprecedented levels and precision, which make our understanding of slowing down or reversing vascular ageing become possible. Epigenetic viz. DNA methylation, histone modifications, and non-coding RNA-based mechanisms, is a hallmark of vascular ageing, its deregulation leads to aberrant transcription changes in tissues. Epigenetics mechanisms by mediating covalent modifications to DNA and histone proteins, consequently, influence the sensitivity and activities of signaling pathways in cells and tissues. A growing body of evidence supports correlations between epigenetic changes and vascular ageing. In this article, we will provide a comprehensive overview of epigenetic changes associated with vascular ageing based on the recent findings with a focus on molecular mechanisms of action, strategies to reverse epigenetic changes, and future perspectives.